Reducing metabolic burden in the PACEmid evolver system by remastering high‐copy phagemid vectors. Issue 2 (20th May 2022) - Davenport, Beth India; Tica, Jure; Isalan, Mark
Abstract: Orthogonal or non‐cross‐reacting transcription factors are used in synthetic biology as components of genetic circuits. Brödel et al. (2016) engineered 12 such cIλ transcription factor variants using a directed evolution 'PACEmid' system. The variants operate as dual activator/repressors and expand gene circuit construction possibilities. However, the high‐copy phagemid vectors carrying the cIλ variants imposed high metabolic burden upon cells. Here, the authors 'remaster' the phagemid backbones to relieve their burden substantially, exhibited by a recovery in Escherichia coli growth. The remastered phagemids' ability to function within the PACEmid evolver system is maintained, as is the cIλ transcription factors' activity within these vectors. The low‐burden phagemid versions are more suitable for use in PACEmid experiments and synthetic gene circuits; the authors have, therefore, replaced the original high‐burden phagemids on the Addgene repository. The authors' work emphasises the importance of understanding metabolic burden and incorporating it into design steps in future synthetic biology ventures.